2019
DOI: 10.3389/fgene.2019.01209
|View full text |Cite
|
Sign up to set email alerts
|

The African Genomic Medicine Training Initiative (AGMT): Showcasing a Community and Framework Driven Genomic Medicine Training for Nurses in Africa

Abstract: The potential of genomic medicine in improving the quality of healthcare both at population and individual-level is well-recognized globally. However, successful adoption of genetic and genomic evidence into clinical practice depends on training the healthcare workforce and clinical researchers in genomic medicine. Due to limited expertise in the medical genetics and genomics field, widespread uptake largely depends on task-shifting for the implementation of genomic medicine implementation to key healthcare pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(24 citation statements)
references
References 40 publications
0
17
0
Order By: Relevance
“…A survey on Canadian physicians working in oncology, cardiology, and family medicine concluded that physicians with prior training on genomics medicine had a significantly higher mean knowledge score [ 56 ]. In fact, education and training are the foundation of most of the platforms, frameworks, and consortia that coined the implementation of genetic testing and personalized medicine [ 57 , 58 , 59 , 60 ].…”
Section: Discussionmentioning
confidence: 99%
“…A survey on Canadian physicians working in oncology, cardiology, and family medicine concluded that physicians with prior training on genomics medicine had a significantly higher mean knowledge score [ 56 ]. In fact, education and training are the foundation of most of the platforms, frameworks, and consortia that coined the implementation of genetic testing and personalized medicine [ 57 , 58 , 59 , 60 ].…”
Section: Discussionmentioning
confidence: 99%
“…Several programmes in Africa can be taken advantage of, including the Human Heredity and Health in Africa (H3Africa) bioinformatics network training and education programmes 44 and their associated networks, African Genomic Medicine Training Initiative (AGMT), 54 the Wellcome Trust-led Developing Excellence in Leadership and Genetics Training for Malaria Elimination in Sub-Saharan Africa (DELGEME), 55 graduate pro grammes and short courses offered under the South African National Bioinformatics Institute (SANBI) and other universities, 56,57 training programmes by genomics institutions such as Kwazulu-Natal Research Innovation and Sequencing Platform (KRISP), the African Center of Excellence for Genomics of Infectious Disease (ACEGID), 58 and Medical Research Council-The Gambia, 59 among others.…”
Section: Infrastructure and Human Capacity Building Sequencing Data mentioning
confidence: 99%
“…The current and projected shortage of medical geneticists and genetic counselors, who historically have provided the majority of genetic services, has created a need for genomic education of health-care professionals across disciplines ( 91 , 92 ). The African Genomic Medicine Training (AGMT) Initiative, for example, was established to develop knowledge and skills of non-specialist providers in genomic medicine ( 93 ). Indigenous people, especially those living in rural and remote areas, have poor access to health services ( 94 ) and little to no access to genetic health services.…”
Section: Introductionmentioning
confidence: 99%